EXTENSIVE AND INTENSIVE LISTENING (Modern education and development, 2025)
This article examines the concepts of extensive and intensive listening in the context of language learning. It explores their definitions, benefits, and applications, backed by relevant literature and practical insights. The study employs qualitative methods to analyze the effectiveness of these approaches and provides actionable recommendations for educators and learners.